1996
DOI: 10.1007/bf00311992
|View full text |Cite
|
Sign up to set email alerts
|

Development of a de novo tumorous necrotic lesion in the liver after transcatheter arterial embolization combined with iodized oil infusion: Report of a case

Abstract: We report herein the case of a 69-year-old woman in whom a hepatic tumorous necrotic lesion was discovered following transcatheter arterial embolization combined with iodized oil infusion (Lp-TAE) for a hepatoma. The lesion, which had not been evident prior to the Lp-TAE, was resected and analyzed pathologically. The portal area distribution in the necrotic lesion was the same as that in the surrounding hepatic tissue, suggesting that the lesion was derived from the nonneoplastic hepatic tissue. Moreover, exte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1998
1998
2013
2013

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…[1][2][3][4] This treatment can be applied to hepatocellular carcinoma (HCC) with multicentric carcinogenesis or intrahepatic metastasis, unresectable multiple metastases, and other lesions with impaired liver function. Compared with other minimally invasive treatments such as percutaneous ethanol injection therapy [5][6][7] or chemoembolization, [8][9][10][11][12] MCT has been evaluated to offer potentially complete tumor ablation. Initially, the indication had been for tumors less than 3 cm in diameter; 1 however, it has now extended to include HCCs larger than 5 cm in diameter.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4] This treatment can be applied to hepatocellular carcinoma (HCC) with multicentric carcinogenesis or intrahepatic metastasis, unresectable multiple metastases, and other lesions with impaired liver function. Compared with other minimally invasive treatments such as percutaneous ethanol injection therapy [5][6][7] or chemoembolization, [8][9][10][11][12] MCT has been evaluated to offer potentially complete tumor ablation. Initially, the indication had been for tumors less than 3 cm in diameter; 1 however, it has now extended to include HCCs larger than 5 cm in diameter.…”
Section: Introductionmentioning
confidence: 99%
“…[12][13][14][15] Seki et al 8 reported two cases of hepatic infarction after PEIT for HCC. In both patients, TAI with SMANCS/Lipiodol had been performed previously.…”
Section: Discussionmentioning
confidence: 98%